Forming an Integrative Training Concept:: A case study of the training in psychotherapy integration - Kostínková, Jana; Roubal, Jan (European Journal for Qualitative Research in Psychotherapy, 2018)
The literature on the nature of integrative psychotherapy training is patchy with limited attention paid to how integrative elements are conceptualized and taught. This study aimed to explore the nature of how integrative psychotherapy understandings are nurtured by trainers. A collaborative action research process was engaged examining the work of one team of trainers in the Czech Republic via several sources of data: 1) a three-year-long e-mail correspondence between trainers; (2) recordings of trainer team meetings focusing on the training concept; (3) focus group interviews conducted by the first author before the training started; and (4) materials for professional accreditations. Data analysis was carried out using Atlas.ti qualitative analytical software and through dialogue between authors. Participants were provided with the analysis results so they could validate them and their feedback was incorporated into the final results. Findings revealed that the individual path to each trainer’s integration foreshadows subsequent teaching. Then within the team, a collaborative approach was taken to identify a common approach to integration and ways of nurturing a shared training identity. Hindering factors were also identified recognizing how doubts about integration are balanced by stabilizing factors such as the use of the accreditation process and emphasis on an approach of dialogue, humility and openness.